An investigation on cryptographic algorithms usage in IoT contexts - Aswathy, R H; Malarvizhi, N (International Journal of Engineering and Technology, 2018)
The broad vision of IoT focuses the highly increasing the electronic devices and application in which leads to the growth of technology. The enormous amounts of constrained devices are interlinked, communicate and coordinate with each other to fulfill its tackier mainly concentrate on low energy, Resource constraint, self-organization and short range of communication. In this heterogeneous environment of Antiprivacy and security are the greatest challenge. The secure information exchange is most critical pitfall to ensure the system security. In this paper we discussed and analyzed about various security algorithms like Triple DES, AES, Blowfish and ECCwith their structure, block size, key generation, number of rounds with different settings. In order to analyze the efficiency of all said algorithms, we made an experiment on algorithms works on constrained devices in different contexts, all our experiments show that ECC is the most suitable security algorithm in IOT contexts.